TRACE ELEMENTS IN THE FANDYUSHKINSKOE POLE COAL DEPOSIT (BERING COAL BASIN, CHUKOTKA) - Daria A. Skiba; Evgenia V. Kuzevanova; Evgeniy P. Shishov (Izvestiya Tomskogo Politekhnicheskogo Universiteta Inziniring Georesursov, 2021)
Relevance. The study of possibility of complex processing of coals of Bering coal basin for extracting rare metals and various trace elements is caused by the necessity of economic development and improvement of security of the Chukotka Autonomous Region. This is especially important in the context of its geographical location in the Far North and its poor accessibility. Nowadays, due to their relatively high cost of production and increased ash-content (up to 30%), the coals of the lower members of the Fandyushkinskoe Pole coal deposit are in low demand in the market, although they make up a significant part of the reserves. The potential opportunity to evaluate these coals also for presence of useful additional elements could increase the value of the extracted raw materials. The aim of the research is to determine the prospects of the territory from the point of view of increased content of trace elements and to identify the areas for the further research. Objects: the Bering coal basin, Late Cretaceous coal deposits of the Alkatvaam coal-bearing region, the Fandyushkinskoe Pole coal deposit and its flanks. Methods: samples collection, construction of lithological columns and sections, instrumental neutron activation analysis. Results. The authors have given the geochemical characteristics of the coals of the Fandyushkinskoe Pole coal deposit (the Alkatvaam coal-bearing region, the Chukotka Autonomous Region) based on the data obtained by instrumental neutron activation analysis. It was discovered that in the coals of the Fandyushkinskoe Pole field deposit of the Bering coal basin and its flanks, concentrations of zinc, strontium, hafnium, scandium and rare earth elements can be at the level of minimum industrial grade in identified types of ores. The data on content of some trace elements in coals of the studied deposit are published for the first time.